Prejudice reduction in an educational setting. Practical outcomes from theoretical approaches - Wójcik, Małgorzata; Popiołek, Katarzyna (Department of Psychology, University of Wrocław, 2014)
Our paper reviews research studies that have investigated interventions aimed at prejudice reduction. The theories and research results are summarized in the following categories: intergroup contact, social identity, and categorization. The intergroup contact approach inspired such techniques as contact hypothesis, jigsaw classroom, Pettigrew’s model, contact with transgression, and imagined intergroup contact hypothesis; while social identity gave the ground for common ingroup identity and crossed categorization theories. We place special emphasis on methods applicable for a school setting, and try to answer the questions: when, why and under which condition will a given method work.
Keywords: recategorization; prejudice reduction; intervention; decategorization; intergroup contact